2001
DOI: 10.1116/1.1368673
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of effects of bias polarization and chemical parameters on morphology and filling capability of 130 nm damascene electroplated copper

Abstract: Through elucidating the effects of current density, cupric ion concentration, bath temperature, and air agitation on plating uniformity and filling capability of copper electroplating, the deposition of copper in an acid copper electrolyte will be illustrated to scale down to the sub-0.13 m features with uniform plating, which is required by chemical mechanical polishing in current damascene techniques. In order to achieve the defect-free filling in sub-0.13 m vias and trenches, the electrolyte must be compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Too low current density cannot provide significant overpotential to obtain denser deposits; however, when too much current is supplied, cupric ions are reduced too fast and Cu aggregation occurs around the protrusion on the surface under higher electric field, thus leading to deposits with rough and porous structures. 5 Figure 2͑b͒ also shows that the resistivity of those films were consistent with the trend of Fig. 2͑a͒.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Too low current density cannot provide significant overpotential to obtain denser deposits; however, when too much current is supplied, cupric ions are reduced too fast and Cu aggregation occurs around the protrusion on the surface under higher electric field, thus leading to deposits with rough and porous structures. 5 Figure 2͑b͒ also shows that the resistivity of those films were consistent with the trend of Fig. 2͑a͒.…”
Section: Resultssupporting
confidence: 82%
“…As the applied current density increases in both dc and PC plating, Figure 2͑a͒ shows that the grain size became smaller due to an increase of the nucleation rate, resulting in deposits with reduced porosity and finer grains. 5 The deposition time was 5 s for both dc and PC plating in the standard electrolyte, and the frequency and the duty cycle were held at 100 Hz and 50%, respectively, in the PC plating. Too low current density cannot provide significant overpotential to obtain denser deposits; however, when too much current is supplied, cupric ions are reduced too fast and Cu aggregation occurs around the protrusion on the surface under higher electric field, thus leading to deposits with rough and porous structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the formation of uniform copper deposits on the AFM probe could be attributed to the enhanced mass transfer of copper ions with the increase in current density. Litearture reports (Chang, 2001) describe that increase in plating current density increased the surface roughness and reduced the grain size of copper films due to an increase of plating overpotential. Several other researchers have demonstrated that the polarization overpotential increased with increasing the plating current density leading to high copper nucleation rate (Takahashi & Gross, 1999a, 2000Tean et al, 2003;Teh et al, 2001).…”
Section: Effect Of Current Density On Copper Electrodepositionmentioning
confidence: 99%
“…The use of electroplated copper showed a superfilling characteristic in advanced integrated circuits, mainly due to increased electromigration (EM) resistance. [9][10][11][12] Based on fluorinated silica glass (FSG) with a dielectric constant (k) of about 3.7, Cu metallization has been developed in logic devices of 0.13 m technology node. Due to the high resistance resulting from the fluorine reactivity with metal lines such as Al or Cu, organosilicate glass (OSG) with good resistance to oxidation has been developed as below 90 nm technology node devices with low dielectric constant below 2.9.…”
Section: Introductionmentioning
confidence: 99%